Nitrate removal in woodchip denitrification bioreactor – an approach combining mathematical modelling and PI control - Nečiporenko, Anatolij; Ivanauskas, Feliksas; Dabulytė-Bagdonavičienė, Jurgita; Povilaitis, Arvydas; Laurinavičius, Valdas (Journal of Environmental Engineering and Landscape Management, 2022)
A mathematical model of nitrate removal in woodchip denitrification bioreactor based on field experiment measurements was developed in this study. The approach of solving inverse problem for nonlinear system of differential convection-reaction equations was applied to optimize the efficiency of nitrate removal depending on bioreactor’s length and flow rate. The approach was realized through the developed algorithm containing a nonlocal condition with an incorporated PI controller. This allowed to adjust flow rate for varying inflow nitrate concentrations by using PI controller. The proposed model can serve as a useful tool for bioreactor design. The main outcome of the model is a mathematical relationship intended for bioreactor length selection when nitrate concentration at the inlet and the flow rate are known. Custom software was developed to solve the system of differential equations aiming to ensure the required nitrate removal efficiency.